Synchronous and asynchronous remote exercise may improve motor and non-motor symptoms in people with Parkinson’s disease during the COVID-19 pandemic - Santinelli, Felipe B.; Simieli, Lucas; Costa, Elisa de C.; Marteli, Leticia N.; Fen, Chien H.; Tardelli, Erica; Okamoto, Erika; Tanaka, Katia; Barbieri, Fabio A. (Brazilian Journal of Motor Behavior, 2021)
BACKGROUND: Stay active is a good strategy to mitigate the negative effects of confinement in people with Parkinson’s Disease (PD). Synchronous (full-time class interaction) and asynchronous (without the live presence of the healthcare professional) exercises are two strategies to avoid the worsening of PD. AIM: To investigate the effect of the synchronous and asynchronous exercise on motor and non-motor symptoms in people with PD during the pandemic lockdown. METHOD: Fifty-eight people with PD responded to an online survey and were divided into synchronous, asynchronous, and no-exercise groups. The participants responded to questions regarding motor and non-motor symptoms, besides the questionnaire of quality of life, physical activity, anxiety and depression, and sleep quality. RESULTS: Synchronous group presents higher amounts of physical activity than the asynchronous and no-exercise groups. Also, the synchronous group presented lower anxiety symptoms, while the asynchronous group presented lower depression symptoms compared with the no-exercise group. Worse motor symptoms were presented by the three groups. CONCLUSION: Stay active during the pandemic lockdown, is beneficial to reduce anxiety and depression symptoms in people with PD. This population should be encouraged to perform synchronous classes to perform greater amounts of physical activity, which in the long-term could produce greater benefits.